2022
DOI: 10.1002/app.52346
|View full text |Cite
|
Sign up to set email alerts
|

EPDM‐g‐MAH toughened bio‐based polyamide 56 to prepare thermoplastic polyamide elastomer and the performance characterization

Abstract: Polyamide is an engineering plastic, which has been widely used in industry and life. Polyamide 56, as a green and environmentally friendly bio-based product, is gradually replacing traditional petroleum-based products. However, in terms of auto parts, communication equipment, and mechanical products, a single polyamide monomer is difficult to meet the end-use standard. EPDM-g-MAH (ethylene propylene diene monomer grafted with maleic anhydride) is melt blended with bio-based polyamide 56 (PA56) in a twin-screw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“… 19 Figure 2 is the infrared spectrum of SMA, TPAE, and their composites. The characteristic spectral bands of SMA at 1778 and 1856 cm –1 are the stretching vibration absorption peaks of carbonyl (C=O) in the acid anhydride group, 20 , 21 while these spectral bands do not appear in composites, which implies that SMA reacts with the hard segment of PA6 in TPAE through the anhydride group. In addition, the peaks at 3290–3300 cm –1 in TPAE and its chain-extended blends correspond to the N–H stretching vibrations, while the sharp peaks at 1638 and 1543 cm –1 separately correspond to the C=O stretching vibrations (amide I) and CO–N–H bending vibration (amide II) induced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Figure 2 is the infrared spectrum of SMA, TPAE, and their composites. The characteristic spectral bands of SMA at 1778 and 1856 cm –1 are the stretching vibration absorption peaks of carbonyl (C=O) in the acid anhydride group, 20 , 21 while these spectral bands do not appear in composites, which implies that SMA reacts with the hard segment of PA6 in TPAE through the anhydride group. In addition, the peaks at 3290–3300 cm –1 in TPAE and its chain-extended blends correspond to the N–H stretching vibrations, while the sharp peaks at 1638 and 1543 cm –1 separately correspond to the C=O stretching vibrations (amide I) and CO–N–H bending vibration (amide II) induced.…”
Section: Resultsmentioning
confidence: 99%
“…Figure is the infrared spectrum of SMA, TPAE, and their composites. The characteristic spectral bands of SMA at 1778 and 1856 cm –1 are the stretching vibration absorption peaks of carbonyl (CO) in the acid anhydride group, , while these spectral bands do not appear in composites, which implies that SMA reacts with the hard segment of PA6 in TPAE through the anhydride group. In addition, the peaks at 3290–3300 cm –1 in TPAE and its chain-extended blends correspond to the N–H stretching vibrations, while the sharp peaks at 1638 and 1543 cm –1 separately correspond to the CO stretching vibrations (amide I) and CO–N–H bending vibration (amide II) induced. It can be observed that the N–H stretching vibration intensity and the peak area decreases, while the CO stretching vibration (amide I) and CO–N–H bending vibration (amide II) intensity and peak area increase in the modified TPAE compared with raw material, which further illustrates that anhydride groups in SMA can react with amino groups in TPAE.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Therefore, it is usually used in automobile parts and filter membrane materials. [17][18][19] However, although pure bio-based PA56 has good comprehensive properties, its application is limited by its low thermal stability and high moisture absorption. 19,20 There have been fewer studies published on bio-based PA56 compared with those on PA6 and PA66.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] However, although pure bio-based PA56 has good comprehensive properties, its application is limited by its low thermal stability and high moisture absorption. 19,20 There have been fewer studies published on bio-based PA56 compared with those on PA6 and PA66. To date, some studies on improving the properties of bio-based PA56 composites have been reported, such as on the improvement of their mechanical properties and yellowing resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-based polyamide (also called nylon) materials have attracted increasing amounts of research attention in the nylon industry. [1][2][3][4] As increasingly sophisticated technologies are applied in the preparation of bio-based monomers, studies on bio-based nylon materials have made exciting breakthroughs. [5][6][7] Bio-based nylons are based on biomass resources such as crops and castor, which is green and sustainable chemistry, and also exhibit similar product performances, such as friction resistance, self-lubricity, and acid and alkali resistance, when compared to traditional petroleum-based nylons.…”
Section: Introductionmentioning
confidence: 99%